How do you solve #x-2y=-1# and #2x-y=4# using substitution?

1 Answer
Jun 1, 2018

Answer:

#x = 3 and = 2#

Explanation:

#x - 2y = -1 - - - eqn1#

#2x - y = 4 - - - eqn2#

Using Substitution Method..

From #eqn1#

#x - 2y = -1 - - - eqn1#

Making #x# the subject of formula;

#x - 2y = -1#

#x = -1 + 2y#

#x = 2y - 1 - - - eqn3#

Substitute #eqn3# into #eqn2#

#2x - y = 4 - - - eqn2#

#2(2y - 1) - y = 4#

#4y - 2 - y = 4#

#4y - y - 2 = 4#

#3y - 2 = 4#

#3y = 4 + 2#

#3y = 6#

#y = 6/3#

#y = 2#

Substituting the value of #y# into #eqn3#

#x = 2y - 1 - - - eqn3#

#x = 2(2) - 1#

#x = 4 - 1#

#x = 3#

Therefore;

#x = 3 and = 2#